IMPLEMENTASI STRATEGI PENERAPAN RITX SOIL & WEATHER SENSOR DI KECAMATAN KADUNGORA, KABUPATEN GARUT, JAWA BARAT - Lina Asnamawati; Is Eka Herawati; Timbul Rasoki; Ana Nurmalia (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2022)
The application of Smart Farming RITX Soil & Weather Sensor technology in Garut is intended to increase agricultural potential. In 2020, farmers still have difficulty using sensor tools by 95%. The percentage of farmer skills is 88.75% that farmers never decide the harvest period based on the results of monitoring weather conditions on a smartphone. Based on this, it is necessary to study the strategy for applying this research method to collect data purposively from 48 farmers, 14 experts namely; 2 academics, 10 agricultural extension workers and 2 community leaders. Using the data analysis method used in this research is descriptive and quantitative methods. The strategy formulation process is carried out through two stages, namely the input stage (analysis of internal external factors) and the matching stage (SWOT analysis). In identifying internal and external factors obtained 6 strengths and 5 opportunities, as well as 7 weaknesses and 10 threats. The results of the study state that the SWOT matrix strategy created to increase strengths and create opportunities in the application of Smart Farming 4.0 Technology in Kadungora District, Garut Regency, West Java Province is as follows; cooperate with the private sector and government to procure inputs (S1,S5,T9), implement features that are simpler and easier to understand by farmers (S2,T1), add demonstration plots in farmers' areas, to prove the benefits of the RITX Soil & Weather Sensor, so that farmers want to apply it to all their lands. (S1, S2, S3, S6, T2), adding training by inviting technology/android-savvy farmer assistants (children/family) and recommending the right provider for the area of ??technology application. (S5, T1, T2 , T3, T5, T7, T8), assistance by experts is carried out from introduction, implementation, repair/detection of damage to obtaining good quantity and quality (S4, S6, T1, T5, T6, T7, T8).